Membangun Budaya Perilaku Positif dan Self Awareness Siswa : Kampanye 'Teman Baik Tidak Membully' - Fida Syaina; Puspita Devi; Fadhil Dzaki Agawan; Yuni Saftika; Ahmad Dani; Femas Okta Wijaya (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service activity aims to build a culture of positive behavior among students through the